2017
DOI: 10.1146/annurev-nutr-071816-064836
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids and NLRP3 Inflammasome–Mediated Inflammation in Metabolic Tissues

Abstract: Worldwide obesity rates have reached epidemic proportions and significantly contribute to the growing prevalence of metabolic diseases. Chronic low-grade inflammation, a hallmark of obesity, involves immune cell infiltration into expanding adipose tissue. In turn, obesity-associated inflammation can lead to complications in other metabolic tissues (e.g., liver, skeletal muscle, pancreas) through lipotoxicity and inflammatory signaling networks. Importantly, although numerous signaling pathways are known to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
153
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 181 publications
(157 citation statements)
references
References 164 publications
2
153
0
2
Order By: Relevance
“…An inadequate intake of vitamin C contributes to small overgrowth, transcytosis of enteric bacteria, and an elevation of lipopolysaccharides, which elicits a low‐grade inflammatory response . On the other hand, saturated fat can activate transmembrane proteins (toll‐like receptors 2 and 4) involved in the activation of the innate immune system, leading to the activation of proinflammatory pathways and the secretion of proinflammatory cytokines, which predispose to adipose tissue inflammation and subsequent insulin resistance …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inadequate intake of vitamin C contributes to small overgrowth, transcytosis of enteric bacteria, and an elevation of lipopolysaccharides, which elicits a low‐grade inflammatory response . On the other hand, saturated fat can activate transmembrane proteins (toll‐like receptors 2 and 4) involved in the activation of the innate immune system, leading to the activation of proinflammatory pathways and the secretion of proinflammatory cytokines, which predispose to adipose tissue inflammation and subsequent insulin resistance …”
Section: Discussionmentioning
confidence: 99%
“…37 On the other hand, saturated fat can activate transmembrane proteins (toll-like receptors 2 and 4) involved in the activation of the innate immune system, leading to the activation of proinflammatory pathways and the secretion of proinflammatory cytokines, which predispose to adipose tissue inflammation and subsequent insulin resistance. 38 The sarcopenia condition of the study participants could be assumed as a chronic condition considering that all subjects of the study were overweight or obese and had metabolic syndrome. Chronic sarcopenia is likely to be associated with permanent and progressive processes such as ageing, obesity, and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐sustained lipolysis orchestrates the accumulation of monocyte‐derived macrophages in the obese WAT, where they polarize or switch from an M2 anti‐inflammatory phenotype toward an M1 pro‐inflammatory phenotype . Such a pathological WAT remodeling particularly occurs with long‐lasting ingestion of Westernized, high‐fat diets (HFDs) rich in saturated fatty acids (SFAs) in both humans and murine models . Conversely, a growing body of evidence points the benefits from replacing dietary SFAs with monounsaturated fatty acids (MUFAs) or omega‐3 polyunsaturated fatty acids (PUFAs) on blood lipid and WAT homeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…Such a pathological WAT remodeling particularly occurs with long‐lasting ingestion of Westernized, high‐fat diets (HFDs) rich in saturated fatty acids (SFAs) in both humans and murine models . Conversely, a growing body of evidence points the benefits from replacing dietary SFAs with monounsaturated fatty acids (MUFAs) or omega‐3 polyunsaturated fatty acids (PUFAs) on blood lipid and WAT homeostasis . This occurrence is likely due to the promiscuity of the master regulator of adipocyte differentiation, the nuclear peroxisome proliferator‐activated receptor γ (PPARγ) in terms of its interaction with selective dietary fatty acids …”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that NLRP3 inflammasome activity is attenuated by mono-and polyunsaturated fatty acids, which are endogenous PPARA agonists (Forman et al, 1997;Kliewer et al, 1997;Mochizuki et al, 2006;Ralston et al, 2017;Shen et al, 2017). Considering these studies, a regulatory mechanism was proposed whereby fatty acids mobilized from adipose tissue during fasting activate PPARA, which in turn suppresses the NLRP3 inflammasome by strong induction of the TXNIP-suppressing lncRNA gene Gm15441, which is antisense to Txnip.…”
Section: Introductionmentioning
confidence: 99%